Subcellular Localization of a Plant Catalase-Phenol Oxidase, AcCATPO, from Amaranthus and Identification of a Non-canonical Peroxisome Targeting Signal - Chen, Ning; Teng, Xiao-Lu; Xiao, Xing-Guo (Frontiers in Plant Science, 2017)
AcCATPO is a plant catalase-phenol oxidase recently identified from red amaranth. Its physiological function remains unexplored. As the starting step of functional analysis, here we report its subcellular localization and a non-canonical targeting signal. Commonly used bioinformatics programs predicted a peroxisomal localization for AcCATPO, but failed in identification of canonical peroxisomal targeting signals (PTS). The C-terminal GFP tagging led the fusion protein AcCATPO-GFP to the cytosol and the nucleus, but N-terminal tagging directed the GFP-AcCATPO to peroxisomes and nuclei, in transgenic tobacco. Deleting the tripeptide (PTM) at the extreme C-terminus almost ruled out the peroxisomal localization of GFP-AcCATPO∆3, and removing the C-terminal decapeptide completely excluded peroxisomes as the residence of GFP-AcCATPO∆10. Furthermore, this decapeptide as a targeting signal could import GFP-10aa to the peroxisome exclusively. Taken together, these results demonstrate that AcCATPO is localized to the peroxisome and the nucleus, and its peroxisomal localization is attributed to a non-canonical PTS1, the C-terminal decapeptide which contains an internal SRL motif and a conserved tripeptide P-S/T-I/M at the extreme of C-terminus. This work may further the study as to the physiological function of AcCATPO, especially clarify its involvement in betalain biosynthesis, and provide a clue to elucidate more non-canonic PTS.